Development of Counting Dakotika Media to Improve Understanding Multiplication Concepts in Class II Elementary School - Syarifah Khoerunnisa; Fitriyani Fitriyani (Pusdikra-Publishing.com, 2023)
This research was motivated by the low understanding of student's concepts in multiplication material and the unavailability of mathematics learning media in schools. This study aims to develop arithmetic dakotika media and find out the results of the use (practicality) and effectiveness of arithmetic dakotika media to improve understanding of the concept of multiplication. This study uses research and development methods with the ADDIE development model. Data collection techniques in this study were observations, interviews, questionnaires (validation and responses), tests and documentation. The result of this study is to produce arithmetic dakotika media which has been declared very feasible or valid by experts (media experts, material experts and language experts) with an average overall score of 97%, arithmetic dakotika media is also stated to be very practical with a score the average is 91.95 %. While the level of effectiveness is 93.1 % so that the arithmetic dakotika media is stated to be very effective. The arithmetic dakotika media that has been developed has been declared very feasible/valid, practical and effective for use in the learning process to increase understanding of the concept of multiplication.